Modernizing Islamic Boarding Schools as a Strategy for Global Transformation: Cultivating Globally-Minded Students in an Era of International Competition - Sutan Akhyar Rajabi; Kautsar Ratu Bilqis; Afif Haniifan; Zayyina Ashfi Qolbina; Nur Aulia Reski (Lembaga Penelitian dan Pendidikan Mandala, 2026)
Pesantren, as the oldest Islamic educational institution in Indonesia, faces the challenge of adapting to globalization and modernization in the 21st century. This research aims to analyze pesantren modernization strategies in preparing globally competitive students without abandoning Islamic identity. The method employed is library research with a qualitative descriptive approach, examining various academic sources related to pesantren educational transformation. The study results show that pesantren modernization includes the integration of traditional curricula with national and international curricula, the development of 21st-century competencies (critical thinking, creativity, collaboration, communication, and digital literacy), strengthening foreign language skills, and the utilization of information technology in learning. Effective transformation strategies include adaptive leadership, the development of international networks, and global alumni empowerment. The research conclusion affirms that moderate integration between tradition and modernization represents an ideal model for producing a generation of Muslims who are moral, critical, digitally literate, and prepared to face global challenges